Chemistry and life : 7th Meeting on Chemistry and Life 2018 : selected, peer reviewed papers from the 7th Meeting on Chemistry and Life 2018, Brno, Czech Republic - Zmeskal, Oldrich (Materials science forum, 2019)
7th Meeting on Chemistry and Life 2018 Selected, peer reviewed papers from the 7th Meeting on Chemistry and Life 2018, Brno, Czech Republic.